2021
DOI: 10.3389/fonc.2021.701998
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Biodegradable, Contrast-Filled Rectal Spacer Balloon in Intensity-Modulated Radiotherapy for Intermediate-Risk Prostate Cancer Patients: Dosimetric Gains in the BioPro-RCMI-1505 Study

Abstract: Background/purposeDose-escalated external beam radiotherapy (RT) is effective in the control of prostate cancer but is associated with a greater incidence of rectal adverse events. We assessed the dosimetric gain and safety profile associated with implantation of a new biodegradable rectal spacer balloon.Materials/methodsPatients scheduled for image-guided, intensity-modulated RT for intermediate-risk prostate cancer were prospectively included in the French multicenter BioPro-RCMI-1505 study (NCT02478112). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Our findings comparable with the first results of the French multicenter open‐label study (BioPro‐RCMI‐1505) using the balloon spacer 13 . In this study reported by Latorzeff et al., 85.2% reduction in the mean rectal rV70 was achieved with the balloon spacer.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings comparable with the first results of the French multicenter open‐label study (BioPro‐RCMI‐1505) using the balloon spacer 13 . In this study reported by Latorzeff et al., 85.2% reduction in the mean rectal rV70 was achieved with the balloon spacer.…”
Section: Discussionsupporting
confidence: 90%
“…Data from the literature provides evidence for these spacer's safety profile, rectal dosimetric gain, and improved quality of life outcomes relative to prostate cancer patients treated with EBRT with no spacer. 3,13 However, there are differences in how the volume between the prostate and rectal interface is created based upon the devices themselves. The implantation procedure of the balloon spacer includes establishing a working channel along the plane from prostate apex to base using a beveled tip dilator dissection with an option for hydro dissection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of patients is important. In these studies, placement of a rectal-prostate spacer was contraindicated in patients at risk of capsular penetration or seminal vesicle invasion (14,15,37). No data exist at this time to support the safety of spacer use in patients with prostate cancer with capsular penetration or seminal vesicle invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Another prostate rectal spacer that has been extensively studied in preclinical and clinical trials is the ProSpace biodegradable fillable balloon [ 54 , 55 ]. The ProSpace system—a deflated balloon made of biodegradable polymer—is placed perineally with hydrodissection and the use of an introducer.…”
Section: Other Available Spacersmentioning
confidence: 99%